Analisis Penawaran dan Permintaan Pariwisata (Studi Kasus di Desa Wisata Tipang Kecamatan Baktiraja Sumatera Utara) - Ropatina Monika Valentina Hutasoit; Muhammad Irfan Affandi; Maya Riantini (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This research intends to examine the availability and state of tourism supply and demand components in Tipang Tourism Village, Baktiraja Sub-district, to support or facilitate the development/growth of tourism villages. Tipang Tourism Village has considerable potential, but tourism development in this area still faces various obstacles, including the low quality and availability of tourist support facilities. Analyzing supply and demand components is crucial for pinpointing areas that require enhancement. To attract more tourists and support local economic growth. The research method employed is a questionnaire survey of visiting tourists and direct observation of each tourism sub-component. The results show that the supply component in Tipang Tourism Village has a score of 32, which means that the supply component is not optimal in supporting the development of tourism villages. Conversely, the demand aspect has a score of 31, indicating inadequacy in supporting tourism development. The components with high scores in supporting development are Penatapan Gonting tourist attractions, places to eat/restaurants, private vehicles as modes of transportation, and social media as promotional media. Conversely, other components have a low value because they are less attractive to tourists, rarely visited, or have unsatisfactory conditions. According to the BCG matrix analysis, the position of tourism activities in Tipang Tourism Village is in the Dogs quadrant, which indicates low supply and demand. Therefore, substantial investment is required to increase market share and tourism growth.